LEARNING MEDIA DEVELOPMENT OF BIOLOGY - Apdoludin Apdoludin (Journal Of Language Education and Development (JLed), 2023)
This research is based on students class XI Mathematics and Natural Sciences, who have difficulty understanding the material of human respiratory system. the results of interviews with biology teachers obtained data that the absence of instructional media in the form of biology book based on mind map on human respiratory system materials for students class XI Mathematics and Natural Sciences for senior high school eleven of Jambi city. Therefore it is necessary media of learning that can help student to understand material of human respiration system. This study aims to develop, determine the feasibility and know the teacher response and student responses to products developed. The type of research is development research using the ADDIE development model. Types of research data in the form of quantitative data and qualitative data. The instrument used is an open questionnaire and closed questionnaire in the form of Likert scale. While the data analysis used in the form of descriptive analysis technique. The results of validation by the material expert obtained an average score of 3.27 included into the category "feasible". The results of validation by the media expert obtained an average score of 2.95 including the category "feasible". Furthermore, the test of biology teacher's response obtained an average score of 91.29 including the "good" category and the student's response test obtained an average score of 90.43 including the "good" category.